Future Teacher Competency Of Vocational Education: Literature Review - Warda Indadihayati (Institut Agama Hindu Negeri Tampung Penyang Palangkaraya, 2024)
Globalisation era without boundaries, Technological advancement modernises different factors in life and affects many areas, including vocational education. Therefore, TVET teachers should enhance their competencies to present vocational training that can facilitate future human capital and adapt to new technologies and global challenges in this digital era. Urgency development educational teacher competence vocation need noticed in ensure quality education expected vocation. Method in this article used in this literature review refer to Prisma method used to do literature review and meta-analysis activities so that make it easy in review goal roadmap structure. result of discussion this more carry on discuss about development trends technology, directions teacher vocational education competence development, development strategy vocational education competencies.